2020
DOI: 10.1088/1755-1315/507/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and management mechanisms for the digital transformation of economic activities

Abstract: The study is devoted to the development of digital technologies in the forest industry, which potential in Russia is practically not measured and belongs to the state ownership at all. The work revealed that forests are exposed to fires, illegal logging, flooding, the spread of diseases, etc. every year, which requires state and regional structures to constantly monitor and control the state of the forest fund. The study conducted an analysis of indicators related to the state of the forest fund, which reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…We suppose that task solution concerns not only forming the organization structure (project office) but also including the stage of planning into the process of making decision, in particular according to group review, while participant take part in project execution. Moreover researchers also propose to create a multilevel system of vertical projects management in the terms of economy digitalization [8,12].…”
Section: Discussionmentioning
confidence: 99%
“…We suppose that task solution concerns not only forming the organization structure (project office) but also including the stage of planning into the process of making decision, in particular according to group review, while participant take part in project execution. Moreover researchers also propose to create a multilevel system of vertical projects management in the terms of economy digitalization [8,12].…”
Section: Discussionmentioning
confidence: 99%
“…But as the literature review showed, no attention was paid to the development of technology for the production of fruit jelly from sea buckthorn berries and feijoa fruits. Our research is carried out for the first time for the production of dietary fruit jelly from this type of raw material [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%